Hemoglobin Levels in Patients with Chronic Kidney Failure Undergoing Hemodialysis Therapy at RSUD Ciamis - Endang Octaviana Wilujeng; Putri Lismayanti (Mukhtabar Journal of Medical Laboratory Technology, 2025)
Background & Objectives: The prevalence of chronic kidney failure in Ciamis Regency based on medical records data from Ciamis Regional General Hospital in 2023 was 318 patients. In kidney failure, the level of erythropoietin produced will decrease and have an impact on the decline in red blood cell production, a condition that also causes a decrease in hemoglobin levels. Clinically, hemoglobin levels are used to determine anemia. If hemoglobin levels are low, the oxygen supply is insufficient and can lead to anemia. The purpose of this study was to determine hemoglobin levels in patients with chronic kidney failure undergoing hemodialysis therapy. Method: This study is a descriptive study using purposive sampling techniques and was conducted at the Hematology Laboratory of STIKes Muhammadiyah Ciamis in May 2024. The respondents in this study were 39 people with chronic kidney failure at Ciamis Regional General Hospital. Results: The results obtained from 39 respondents with chronic kidney failure undergoing hemodialysis therapy at Ciamis Regional General Hospital were below normal levels. Conclusion: From the results of this study, it can be concluded that there were 14 people with mild anemia with Hb levels >10 g/dl, and 25 people with moderate anemia with Hb levels of 7-10 g/dl.